2021
DOI: 10.1186/s40545-021-00296-w
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding a Med-Wreck: a structured medication reconciliation framework and standardized auditing tool utilized to optimize patient safety and reallocate hospital resources

Abstract: Background The incidence of preventable adverse drug events (ADE) is approximately one medication error per patient per hospital-day. A quality medication reconciliation (MedRec) process is a crucial intervention used to reduce ADE in the hospital and community setting. Amid the coronavirus disease 2019 (COVID-19) pandemic, preventing medication errors is vital to avoid patient readmission, reduce disease complications, and reduce cost and patient burden on the healthcare system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In the U.S., the incidence of preventable adverse drug events from medication errors in hospitalized patients is estimated to be approximately one medication error per patient per day. 12 , 13 These events can cause increased length of hospital stay, increased mortality risk, and higher costs. One technique for medical reconciliation is to include a pharmacist in the process.…”
Section: Discussionmentioning
confidence: 99%
“…In the U.S., the incidence of preventable adverse drug events from medication errors in hospitalized patients is estimated to be approximately one medication error per patient per day. 12 , 13 These events can cause increased length of hospital stay, increased mortality risk, and higher costs. One technique for medical reconciliation is to include a pharmacist in the process.…”
Section: Discussionmentioning
confidence: 99%
“…interview with the patient occurred in less than half of all MedRec (45.7%) [ 29 ]. Moreover, a very recent study revealed no implementation of MedRec in any of the observed sites [ 30 ]. Important barriers for MedRec implementation mentioned were: lack of awareness, a designated MedRec team and insufficient knowledge of health care professionals [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to gathering a BPMH, include a lack of: trained and experienced medication history staff, complete medication history resources, patient acuity and compliance, pharmacy hours of operation, time to implement new BPMH best practices, and con icting accounts from the patient or caregivers as to which medications the patient is actively taking [9]. In addition to everyday challenges, there are many ways in which the COVID-19 pandemic forced hospital systems to change medication history clinical work ows, including conducting virtual medication history interviews with patients, as well as sta ng challenges due to clinician burnout [7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most important step to a productive and clinically accurate medication reconciliation, is a complete and accurate medication history assessment upon admission to the hospital, or a Best Possible Medication History (BPMH) [5]. Several studies have shown that the vast majority of inpatient medication errors stem from discrepancies within a patient's medication history list [2,[6][7][8]. Barriers to gathering a BPMH, include a lack of: trained and experienced medication history staff, complete medication history resources, patient acuity and compliance, pharmacy hours of operation, time to implement new BPMH best practices, and con icting accounts from the patient or caregivers as to which medications the patient is actively taking [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation